Identification of a Novel Non-V600E BRAF Mutation in Papillary Thyroid Cancer - Marco Capezzone; Maja Rossi; Elisabetta Macerola; Silvia Cantara; Francesco Pepe; Eugenia Maria Morabito; Gilda Dalmazio; Sara Bardi; Agostino Ognibene; Massimo Alessandri; Gabriele Materazzi; Luigi De Napoli; et al. (Case Reports in Endocrinology)
Papillary thyroid cancer (PTC) is a common endocrine malignancy, and its incidence is reported to be constantly increasing. BRAF mutation is detected in approximately 44% of PTCs, and the most common BRAF mutation is thymine (T) to adenine (A) missense mutation in nucleotide 1796 (T1796A, V600E). Although BRAFV600E represents 95% of all BRAF mutations, uncommon BRAF mutations have been reported in thyroid carcinomas and represent an alternative mechanism of BRAF activation with unclear clinical significance. We report a novel non-V600E mutation (c.1799_1812delinsAT, p.V600_W604delinsD), identified preoperatively with next-generation sequencing (NGS) on the material obtained with fine-needle aspiration cytology (FNAC) performed on a thyroid nodule cytologically suspicious for malignancy in a 35-year-old male patient. The presence of this new variant of BRAF mutation was subsequently confirmed in the postoperative phase by direct Sanger sequencing. In conclusion, we report a new non-V600E variant previously undetected in papillary thyroid cancer. In addition, this case report shows that the NGS technique on cytological tissue allows to detect the presence of rare mutations, thus increasing the diagnostic specificity of molecular analysis.